DEVIANT BEHAVIOR OF ADOLESCENTS (general characteristics) - Orsayeva Raissa Anuarovna; Saduakasova Laila Kumarbekovna; Duisembayeva Samal Dauletovna (Modern Scientific Technology, 2025)
The article is devoted to the study of the tendency to dependent behavior in deviant teenager. In the article is being considered dependent behavior refers to the teenager desire to escape reality by changing his or her mental state through the use of chemicals